Limited predatory effects on infaunal macrobenthos community patterns in intertidal soft‐bottom of Arctic coasts. Issue 1 (24th January 2023) - Díaz, María José; Buschbaum, Christian; Renaud, Paul E.; Valdivia, Nelson; Molis, Markus
Abstract: Predation shapes marine benthic communities and affects prey species population dynamics in tropic and temperate coastal systems. However, information on its magnitude in systematically understudied Arctic coastal habitats is scarce. To test predation effects on the diversity and structure of Arctic benthic communities, we conducted caging experiments in which consumers were excluded from plots at two intertidal sedimentary sites in Svalbard (Longyearbyen and Thiisbukta) for 2.5 months. Unmanipulated areas served as controls and partial (open) cages were used to estimate potential cage effects. At the end of the experiment, we took one sediment core from each plot and quantified total biomass and the number of each encountered taxon. At both sites, the experimental exclusion of predators slightly changed the species composition of communities and had negligible effects on biomass, total abundance, species richness, evenness, and Shannon Index. In addition, we found evidence for cage effects, and spatial variability in the intensity of the predation effects was identified. Our study suggests that predators have limited effects on the structure of the studied intertidal macrobenthic Arctic communities, which is different from coastal soft‐bottom ecosystems at lower latitudes. Abstract : Predation is a key modifier of community dynamics, but information on its magnitude on community regulation in the systematically understudied Arctic coastal habitats. To test the magnitude and direction of the effects of predation on the structure of Arctic benthic communities, we conducted caging experiments in which consumers were excluded from plots at two sites in Svalbard, Arctic. This study suggests that consumers have limited effects on the structure and functioning of the intertidal benthic Arctic communities.